Determinants of poverty in rural cocoa farming communities in Ghana: unidimensional and multidimensional analysis - Solomon Yaw Agyeman-Boaten (Cogent Economics & Finance, 2024)
Poverty is a rural phenomenon due to the dominance of subsistence farming in rural communities. This study compares the estimates of unidimensional and multidimensional methodologies to analyse the factors that influence the poverty levels of cocoa farming households predominantly in rural Ghana. A census was conducted in the Chorichori community in Ghana using a structured questionnaire to gather information from 386 cocoa farming households. The multidimensional poverty index and expenditure-based poverty measures were used to estimate a bivariate probit regression to find the determinants of cocoa farming households' poverty. The study's outcome indicates that poverty among the cocoa farmers is jointly determined, unidimensionally and multidimensionally, by the access to healthcare, household child deaths, household's school-age child not in school, access to farm inputs, and the age of the household head. Whereas the education level of the household head, frequency of ill-health, use of external labour, migration status, and relationship to the household head were significant in determining multidimensional poverty, the number of household members, cooperative union membership, access to farm water, occupational diversity, household access to financial credit, and the marital status of the household head significantly determined unidimensional poverty among the cocoa farmers. Even though both poverty measures produced fairly different results, the study's findings showed the mutual and exclusive importance of the unidimensional and multidimensional poverty approaches in determining poverty and formulating good developmental policies for cocoa farmers. Therefore, selecting an approach should be based on prevailing circumstances, such as differences across locations and within households or entities. This research provides critical insights into the complex nature of poverty among cocoa farming households in rural Ghana. By comparing unidimensional and multidimensional poverty measures, the study reveals significant disparities in how poverty is assessed, offering a more comprehensive understanding of the socio-economic challenges faced by rural communities. This dual approach not only uncovers the socioeconomic factors that contribute to poverty but also reveals discrepancies and complementarities between different poverty measurement methods, offering a nuanced perspective that can enhance the accuracy of poverty assessments. The findings highlight the need for policymakers, development agencies, and social planners to target interventions that address the specific factors contributing to poverty in rural areas, thereby improving the effectiveness of poverty alleviation programs. By informing more holistic and inclusive policies, this study supports efforts to reduce poverty among rural cocoa farmers, ultimately contributing to broader economic development and social equity in Ghana and similar contexts across developing countries.
Keywords: C31; I32; O13; Q12; Q14; 330; Bivariate probit regression; determinants; cocoa farmers; multidimen-sional poverty; rural areas; unidimensional poverty